Analisis Kapasitas Produksi Alat Berat Pada Pekerjaan Galian Dan Pekerjaan Lapis Pondasi Agregat Dalam Peningkatan Struktur Jalan Madupat-Camplong Kabupaten Sampang - Zabadi, Fairus; Ahmad Fatoni (Jurnal Teknik Sipil, 2025)
The use of heavy equipment is an important factor in facilitating and accelerating the process of a job, especially on large-scale projects and limited time. Work with the use of heavy equipment aims to facilitate the work, so that the expected results can be achieved more easily in a relatively shorter time. The study uses qualitative descriptive. The source of research data was obtained from secondary data and primary data. Data collection was obtained from literature reviews, interview results and observations. The data analysis used was to find the value of production capacity based on the provisions of PUPR Regulation No. 1 of 2022. In this study, what was observed were the factors that determined the value of the production capacity of each heavy equipment in the Madupat - Camplong Road Structure Improvement project, Camplong District. The results of the analysis obtained were, for excavation work, using excavator heavy equipment with a production capacity of 189 m³ / day, a work period of 5 days, and a rental price of Rp. 15,500,000, Dump Truck with a production capacity of 77.77 m³ / day, a work period of 11 days, and a rental price of Rp. 6,600,000, while for aggregate foundation layer work using excavator heavy equipment with a production capacity of 378 m³/day, work duration of 4 days, and equipment rental price of Rp. 10,800,000, Wales (Three Wheel Roller) with a production capacity of 246.96 m³/day, work duration of 6 days, and equipment rental price of Rp. 6,100,000.